Mass. Gen. Laws, ch. 194, § 1 (1850), codified at Mass. Gen. Stat. 816, ch. 164 § 10 (1873) - (:unkn) unknown (My University, 1850)
Enhanced the sentence of anyone carrying slung-shot, metallic knuckles, billies, or other dangerous weapons while committing a criminal offense or arrested upon warrant of a magistrate. Violators fined not exceeding fifty dollars or imprisonment not exceeding one year.
Keywords: CARRY - INTENT TO COMMIT CRIME